The Study Of Consumer Protection In The Mystery Box Sale And Purchase Agreement On Shopee Marketplace Viewed From Indonesian Law - Afiq, Muhammad Adib; Najib Imanullah, Moch. (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
This study analyzes the Consumer Protection Study on the Mystery Box Sale and Purchase Agreement on the Shopee Marketplace viewed from Indonesian Law. This research is a normative legal research using secondary data sources through library research. The results of the study show that the Mystery Box Sale and Purchase Agreement in the Shopee marketplace violates the provisions of Article 1320 of the Civil Code regarding the element of